Unveiling Trends and Knowledge Structure in Commodity Derivatives Research: Insights from Bibliometric Analysis - Hartono, Pierdijono; Utama, Wahyudayanto; Heryana, Toni; Medidjati, R. Adam (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Research on commodity derivatives has grown steadily due to increasing market complexity and investor interest. This study aims to examine trends, patterns, and scholarly impact in commodity derivatives research from 1999 to 2023. Using 105 articles retrieved from the Scopus database, bibliometric analysis was conducted with Excel, Python, and RStudio to assess publication growth, citation patterns, journal quartiles, geographic distribution, leading authors, and institutional affiliations. Results show a consistent increase in research activity, with the Journal of Futures Markets being the most influential journal. The UK, USA, and the Netherlands are the top contributing countries, while Q1 and Q2 journals dominate publication platforms. Leading institutions include the University of Technology Sydney, North-West University, and the Austrian Foundation for Development Research (ÖFSE). The study provides a comprehensive mapping of the field, highlighting key journals, authors, and institutions. Practical implications include guidance for researchers, practitioners, and policymakers in selecting journals for submission, identifying collaboration opportunities, and tracking emerging research trends. Limitations involve reliance solely on Scopus data; future studies could expand to other databases, such as Web of Science and Google Scholar, for broader insights.